Homicidal deaths due to weapons: an autopsy-based study - Hossain, Din Islam; Jeba, Tasfia Razzak; Dey, Suranjit; Tasnim, Zakia; Tabassum, Taniza (International Journal of Research in Medical Sciences, 2024)
Background: Homicide, one of the oldest crimes in human civilization, involves the killing of one human being by another. Defined legally as the intentional destruction of human life, it is a leading cause of unnatural deaths worldwide. The crime involves two key elements: Mens rea (preplanning) and Actus reus (execution). Homicidal methods and patterns vary globally, influenced by factors such as weapon availability, motives, cultural and social influences, and socio-economic status. Violence is recognized as a global public health issue, contributing to significant mortality and disability, with approximately 520,000 people dying annually from interpersonal violence. The study aims to explore the types of injuries, weapons, and anatomical regions of the affected victim. Methods: This retrospective observational study was conducted at the department of forensic medicine, Dhaka medical college and hospital, Dhaka, Bangladesh, focusing on 120 autopsied homicide cases involving definite weapons from January 2021 to December 2023. The study included all age groups, excluding accidental burn deaths, suspected homicidal poisonings, and decomposed bodies. Data were gathered from police inquest and post-mortem reports, analyzing injury types, weapons used, and their anatomical distribution. The findings were correlated with victims' age and gender. The ethics committee approved the study, and data were presented using SPSS for statistical analysis. Results: The study analyzes violent incidents, focusing on participant demographics, weapon types, injury patterns, and homicide intentions. The highest participant age group is 21-30 years (33.33%), with males dominating at 84.17%. Knives are the most used weapon (51.67%), followed by blunt objects (38.33%). Head injuries are most common (44.17%), with intracranial hemorrhage (ICH) as the leading cause of death (48.33%). Non-intentional homicides constitute 60%, while 35.83% are deliberate. The study provides detailed insights into the nature and causes of homicides in the population studied. Conclusions: The study in Dhaka, Bangladesh, reveals that young males are the primary victims of homicide, with knives and blunt objects frequently used. Head injuries, especially ICH, are the leading cause of death. The findings call for targeted interventions and further research into the factors driving non-intentional homicides.